Genetic control on number of days to flowering and yield components in common bean (Phaseol vulgaris L.) - Barelli, Marco Antonio Aparecido; Vidigal, Maria Celeste Gonçalves; Amaral Júnior, Antonio Teixeira do; Vidigal Filho, Pedro Soares; Silvério, Lucas (Acta Scientiarum. Agronomy, 2008)
Genetic control on the performance of six common bean cultivars (LPSPI 93-17, LPSPI 93-19, FT Nobre, Aporé, Rudá and Campeão-1) and their 15 diallel hybrids were carried out, based on the following traits: number of days to flowering, mean seed weight, total number of pods per plant, mean number of seeds per pod, mean seed weight and grain yield. Hayman’s methodology (1954) was used for the parameter estimation. The results showed that the dominance effects were important only for the mean seed number per pod. There were high coefficients of genetic determination for number of days to flowering and mean seed weight traits and, therefore, superior lines may be obtained using simple selection methods. Aporé, Rudá and Campeão-1 cultivars should be indicated for intrapopulational breeding programs for grain yield.